FRANCHISING FROM A CUSTOMER PRIVACY PERSPECTIVE - Debora, Debora; Anggusti, Martono; Sitanggang, Adira (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
In the implementation of a franchise agreement, a breach of promise may be committed by either the franchisee or the franchisor. In order to ensure legal protection, the clauses in the agreement must include provisions regarding the limits of use of intellectual property rights. As the most crucial aspect of conducting business operations in the digital age, franchisees and franchisors collect a plethora of customer data, including contact information, purchasing and browsing behavior, location information, and other crucial data, with the objective of driving advertising and growth activities for the franchise system. However, the collection and utilization of this data can potentially expose franchisors and franchisees to a multitude of risks. In an increasingly digitized world, personal data represents a valuable resource for the development of any business. Personal data can also be regarded as an asset with high economic value. The implementation of a franchise agreement raises legal issues pertaining to the limitations on the use of intellectual property rights by franchisees in the implementation of intellectual property from the franchisor. Another problem is how the franchisee's efforts to protect customer data, which is part of the franchise, are to be reconciled with the rights of the franchisor. This study employs normative juridical research to address the issues under consideration. In addition to the limitations clearly and firmly established in legislation, the agreement that serves as the legal basis also imposes strong restrictions to maintain the legal protection of the parties in the franchise system. The contents of the agreement serve as a guide for the parties in implementing the agreement. Consumers have the right to be protected by business actors, one of which is the protection of their personal data. The protection of personal data is a matter of significant sensitivity, given the numerous instances in which such data must be safeguarded to prevent its leakage. In this regard, the